What is democratic evaluation? - and Picciotto, R. (2013)
This article from Robert Picciotto provides an overview of democratic evaluation, particularly with reference to its use in the European Union context. "Can evaluation strengthen the democratic process? Specifically can it help fill the democratic deficit (limited transparency; weak bureaucratic accountability, etc.) often ascribed to the European Union? First and foremost, evaluators operating in the European space should be committed to the ethical and democratic values of the European project and the promotion of its social inclusion and cohesion ideals. But two other sets of challenges must also be met: those that relate to evaluation in democracy and those that relate to democracy in evaluation. The former has to do with the macro positioning of evaluation processes in society. The latter has to do with the evaluation approaches and methods used in deliberative democratic decision making processes." (Picciotto, 2013)